Blood transfusions and its rational use in obstetrics - Malipatil, Pushpanjali; Malipatil, V. B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Blood transfusion (BT) during or after delivery is a serious and sometimes a predictable event. This study helps to generate the information and knowledge regarding the various aspects of blood transfusions in obstetrics and its rational use and alternative strategies. Methods: This is retrospective study of 184 obstetric patients who had 288 blood transfusions during the month of March and April 2014 in the department of obstetrics in an urban tertiary care referral government teaching institute. Results: During this study period of 2 months from March to April 2014 there were 907 admissions in the labour room and 642 deliveries. Among these, 184 patients received blood transfusions. Numbers of blood transfused were 288. The main indication of blood transfusion was anaemia. Conclusions: As many as 56% of pregnant women are anaemic depending on the geographic and socio-economic group studies. Various strategies can be implemented to reduce the anaemia and decrease the number of blood transfusions so that patient will receive the maximum benefit with minimal risks.